Effects of increased myocardial tissue concentration of myristic, palmitic and palmitoleic acids on the course of cardiac atrophy of the failing heart unloaded by heterotopic transplantation - Pokorný, M; Mrázová, I; Malý, J; Pirk, J; Netuka, I; Vaňourková, Z; Doleželová, Š; Červenková, L; Maxová, H; Melenovský, V; Šochman, J; Sadowski, J; et al. (Physiological research, 2018)
The present experiments were performed to evaluate if increased heart tissue concentration of fatty acids, specifically myristic, palmitic and palmitoleic acids that are believed to promote physiological heart growth, can attenuate the progression of unloading-induced cardiac atrophy in rats with healthy and failing hearts. Heterotopic abdominal heart transplantation (HT(x)) was used as a model for heart unloading. Cardiac atrophy was assessed from the ratio of the native- to-transplanted heart weight (HW). The degree of cardiac atrophy after HT(x) was determined on days 7, 14, 21 and 28 after HT(x) in recipients of either healthy or failing hearts. HT(x) of healthy hearts resulted in 23+/-3, 46+/-3, 48+/-4 and 46+/-4 % HW loss at the four time-points. HT(x) of the failing heart resulted in even greater HW losses, of 46+/-4, 58+/-3, 66+/-2 and 68+/-4 %, respectively (P<0.05). Activation of "fetal gene cardiac program" (e.g. beta myosin heavy chain gene expression) and "genes reflecting cardiac remodeling" (e.g. atrial natriuretic peptide gene expression) after HT(x) was greater in failing than in healthy hearts (P<0.05 each time). Exposure to isocaloric high sugar diet caused significant increases in fatty acid concentrations in healthy and in failing hearts. However, these increases were not associated with any change in the course of cardiac atrophy, similarly in healthy and post-HT(x) failing hearts. We conclude that increasing heart tissue concentrations of the fatty acids allegedly involved in heart growth does not attenuate the unloading-induced cardiac atrophy.
Keywords: Heart Transplantation; Animals; potkani inbrední LEW; Rats; Fatty Acids, Monounsaturated; Myocytes, Cardiac; Heart Failure; srdeční selhání; heterotopická transplantace; Transplantation, Heterotopic; Myristic Acid; Palmitic Acid; Male; transplantace srdce; krysa rodu Rattus; kyseliny mastné mononenasycené; kyselina palmitová; mužské pohlaví; zvířata; Myocardium; myokard; Rats, Inbred Lew; kyselina myristová; kardiomyocyty